Analisis Faktor Faktor Yang Mempengaruhi Keinginan Mahasiswa Dalam Berinvestasi Di Pasar Modal Di Era Pandemi Covid-19 - erwin erwin; Taufik Hidayat B Tahawa (MANDAR: Management Development and Applied Research Journal, 2023)
This study aims to identify and analyze the effect of investment risk, level of income (capital), investment motivation and basic knowledge of investment on investment interest in students of the Faculty of Economics, University of West Sulawesi. The research design is quantitative. The sample in this study were 93 students from the accounting study program and management study program, the Faculty of Economics, University of West Sulawesi, in 2017 and 2020. Data collection in this study used the questionnaire method. Instrument trials were analyzed using validity and reliability tests. The data analysis technique used in this study is the classical assumption, simple linear regression analysis and multiple linear regression analysis. The results of this study indicate that t count with a value of x1 of 4,883, x2 of 5,703, x3 of 2,253 and x4 of 2,401 is greater than the value of t table with a value of 1.662. The significance value of variable x to variable y is below 0.05 so that H1, H2, H3 and H4 can be accepted and it can be concluded that all variables x, namely Investment Risk, Level of Income (Capital), Motivation and Basic Knowledge have an effect on variable y, namely Investment Interest. The ability of the independent variables to explain changes in the dependent variable is 57.40%.